UM SISTEMA DE APOIO A GERÊNCIA DE REQUISITOS ADERENTE AO MPS.BR - Junior, Jailton Almeida Vaz; Universidade do Estado da Bahia (2018)
The quality of a software product is directly related to the process used to develop it. Thus, many companies have been looking for certification in MPS.BR, a process quality model developed to improve the software production capacity of Brazilian companies. However, meeting the requirements of this model is not a trivial task, since it is necessary to fulfill all the results defined there as well as record evidences, which prove those results. Therefore, support systems might be an important resource in maintaining the data needed to show the evidences required by MPS.BR. This article presents software, adhering to the Requirements Management process specified by MPS.BR, to support companies that already have or that want to obtain this certification. The software was evaluated, through a case study, by professionals directly involved with the MPS.BR of a company that has current certification showing adherence to the requirements of the model.